THE INFLUENCE OF LOAN TO DEPOSIT RATIO AND DEBT TO EQUITY RATIO ON RETURN ON EQUITY AT PT BANK NEGARA INDONESIA (PERSERO) TBK FOR THE PERIOD 2014–2023 - Eni Puji Astuti; Rahmi Hermawati; Rima Handayani (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the influence of the Loan to Deposit Ratio (LDR) and Debt to Equity Ratio (DER) on Return on Equity (ROE) at PT Bank Negara Indonesia (Persero) Tbk during the 2014–2023 period. Using a descriptive quantitative approach, this research leverages financial statement data from the company over ten years. The analysis involves multiple linear regression, with LDR and DER serving as independent variables and ROE as the dependent variable. The findings reveal that LDR does not significantly affect ROE, indicating that the bank's liquidity in channeling third-party funds into credit does not directly enhance profitability. Similarly, DER does not show a significant influence on ROE, suggesting that financial leverage alone is not a determining factor for profitability. Furthermore, the simultaneous analysis of LDR and DER demonstrates no significant impact on ROE, highlighting the need to consider other factors that might play a more substantial role in influencing financial performance. The results suggest that operational efficiency, credit quality, risk management, and macroeconomic conditions may be more critical determinants of ROE. This study underscores the importance of adopting a comprehensive approach to analyzing financial performance and offers recommendations for improving profitability and competitiveness in the banking sector.